(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The article outlines modern views on the principles of therapy for Helicobacter pylori infection, the resistance of the pathogen, the drugs used, their combinations and effectiveness in achieving remission and reducing the frequency of relapses.